Gonadotropin-Releasing Hormone Receptor Signaling and Functions - Stanko S. Stojilkovic (Frontiers Research Topics, 2018)
This eBook provides a comprehensive overview of our current knowledge on Gonadotropin-releasing hormone receptor evolution, structure, signaling and functions. Apart from review articles, it comprises exciting new research, as well as hypotheses and perspectives, all of which are valuable in guiding our further research in this field.